2017
DOI: 10.1007/s40618-017-0665-3
|View full text |Cite
|
Sign up to set email alerts
|

Prepubertal ultra-low-dose estrogen therapy is associated with healthier lipid profile than conventional estrogen replacement for pubertal induction in adolescent girls with Turner syndrome: preliminary results

Abstract: PurposeThe metabolic effects of prepubertal low-dose estrogen replacement (LE) therapy in Turner syndrome (TS) have not been fully investigated to date. The present study aimed to compare glucose and lipids metabolism in adolescents with TS on LE and conventional estrogen replacement (CE).MethodsIn 14 TS (mean age 13.8), LE (17β-estradiol, 62.5 μg daily) was introduced before age 12 (mean age 10.5), and followed by a pubertal induction regimen after age 12, and in 14 CE was started after age 12 (mean 14, SD 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Analyzing the results of our study, we observed a negative effect of visceral adipose tissue on hand grip strength in the control group, which could not be proven in subjects with TS. Excess body fat, especially visceral fat, is associated with insulin resistance and systemic inflammation, which can impair muscle function [39,40]. In the context of TS, understanding the role of visceral adipose tissue in muscle weakness is crucial, as it can provide insight into strategies to improve muscle strength through weight control and dietary interventions [41].…”
Section: Discussionmentioning
confidence: 99%
“…Analyzing the results of our study, we observed a negative effect of visceral adipose tissue on hand grip strength in the control group, which could not be proven in subjects with TS. Excess body fat, especially visceral fat, is associated with insulin resistance and systemic inflammation, which can impair muscle function [39,40]. In the context of TS, understanding the role of visceral adipose tissue in muscle weakness is crucial, as it can provide insight into strategies to improve muscle strength through weight control and dietary interventions [41].…”
Section: Discussionmentioning
confidence: 99%
“…The current consensus is that if gonadotropins are elevated, treatment should begin at 11-12 years to mimic normal physical and social development without interfering with the effect of growth hormone therapy on final height [16,17]. Although some studies showed the benefits of prepubertal introduction of low-dose estrogen on lipid and metabolic profile and denied its negative impact on final height [18,19], this practice is still under investigation [16]. In this survey, 84.5% would start estrogen for girls aged 11 years and older with TS, with 11-12 years being the most frequently (51.3%) suggested age, while only 5.3% consider it during early/ mid childhood.…”
Section: Discussionmentioning
confidence: 99%
“…In Fig. 4, final height was compared between early (age 10-12 years) and late (from age 12 years) start of oestrogen treatment (EE2 or E2) in a meta-analysis using six studies (108,109,110,111,112,113). Early start of treatment did not result in a clearly lower final height than the late start of treatment (difference −1.0 cm; 95% CI: −4.0 to 1.9 cm).…”
Section: Clinical Question III What Is the Optimal Treatment To Induc...mentioning
confidence: 99%
“…In Fig. 5, BMI was compared between early (age 10-12 years) and late (from age 12 years) start of oestrogen treatment in a meta-analysis using two studies (108,111). The early start of treatment resulted in a lower, though not significantly, BMI than the late start of treatment (difference −0.9 points; 95% CI: −2.7 points to 0.9 points).…”
Section: Clinical Question III What Is the Optimal Treatment To Induc...mentioning
confidence: 99%